DISASTER GOVERNANCE TRANSFORMATION: THE URGENCY OF THE DISASTER MANAGEMENT QANUN FOR ENHANCING REGIONAL RESILIENCE IN PIDIE - Nurmaliasari Nurmaliasari (Jurnal Ikhtibar Nusantara, 2026)
Pidie Regency faces severe vulnerability to annual ecological disasters like floods and landslides, which threaten human lives and cripple the local economy. Ironically, this escalating natural threat collides with paralyzed pre-disaster governance due to the absence of specific regional legal instruments. This policy paper critically dissects the root causes of disaster management issues in Pidie and formulates implementable strategic policy alternatives. Utilizing a qualitative case study approach, data were collected through existing policy document reviews and open-ended questionnaires distributed to 50 key respondents. The data were analyzed using SWOT matrix projections, and the feasibility of policy alternatives was evaluated via the William Dunn method. The study reveals that the absence of a Disaster Management Bylaw (Qanun) has systemically deprived the region of its mitigation autonomy. The government remains trapped in a reactive paradigm because disaster funding is locked by the Unexpected Expenditure (BTT) regulation, which is strictly disbursed only during post-disaster emergencies. This triggers an acute lack of early warning infrastructure and perpetuates reliance on external logistical aid. Based on comprehensive evaluations, this study highly recommends the immediate initiation and ratification of the Pidie Regency Disaster Management Qanun as the absolute solution. This decision is not merely an administrative obligation, but an essential humanitarian endeavor to legalize pre-disaster budget allocations, synergize Village Funds, and transform the local bureaucracy into a visionary protective shield for citizens' safety. Keywords: Public Policy, Disaster Governance, Disaster Management Bylaw, Mitigation, Regional Resilience.